The benefits of playing darts / Nor Hanim Abd Rahman - Abd Rahman, Nor Hanim (Unit Penerbitan Dan Publisiti JSKM, 2023)
Here are some of the benefits of playing darts [i] Improves hand-eye coordination Darts requires a high level of hand-eye coordination and precision, which can improve with regular practice. This skill can also transfer to other activities that require coordination and accuracy, such as playing sports or performing manual tasks.